Expression in yeast (Pichia pastoris) of recombinant Cb-peritrophin-42 and Cbperitrophin- 48 isolated from Chrysomya bezziana (the Old World Screwworm fly) - Sri Muharsini; Tony Voucoloco (Indonesian Center for Animal Research and Development (ICARD), 2000)
Pichia pastoris has been investigated as a means to express recombinant forms of two putative peritrophic membrane antigens from Chrysomya bezziana, Cb-peritrophin-42 (Cb42) and Cb-peritrophin-48 (Cb48). Recombinant Cb48 was expressed as a secreted and glycosylated protein. The yield of recombinant protein was 8 mg per litre of culture. In contrast, recombinant Cb42 was not expressed at detectable levels in Pichia pastoris, probably due to A + T rich sequence which may cause premature transcriptional termination. To expedite Cb42 expression in yeast, Cb42 was divided into two domains: Cb42A and Cb42B. Cb42B was successfully expressed in Pichia pastoris, yielding 0.4 mg per litre of culture. However, Cb42A was not expressed. This work demonstrates that although Pichia pastoris offers considerable benefits as an expression system producing high level of glycosylated protein, success may vary from protein to protein. Key words: Chrysomya bezziana, peritrophin, Pichia pastoris